(untitled) (Practitioner Research, 2019)
Interpersonal, intrapersonal, and communication skills are few examples of soft skills that employees should have to contribute to an organization. Thus, it is important to inculcate soft skills during early years of schooling. Many research focused on inculcating soft skills on students at higher education institutions in preparing them for employment but few has focused on soft skills at primary schools level. This paper discusses a small part of our broader qualitative exploratory that looks into the characteristics of teaching and learning environments in selected primary schools’ mathematics classrooms. Here, we provide a glimpse into two mathematics teachers’ talk or verbal indications which could be interpreted as their latent intentions towards inculcating soft skills competence among students during their mathematics lessons. The findings indicate that there were instances of indications for inculcation of soft skills during the teaching and learning activities. The teachers’ talk provided evidence for the inculcation of probable soft skills which include critical and creative thinking, collaborative effort, cooperation, communication, team working, tolerance and leadership. The findings contribute to field of mathematics learning and instruction that promotes infusion of soft skills within primary schools’ mathematics classrooms.